Electrophoretic processing of chitosan based composite scaffolds with Nb-doped bioactive glass for bone tissue regeneration - Bonetti, Lorenzo; Altomare, Lina; Bono, Nina; Panno, Eliana; Campiglio, Chiara Emma; Draghi, Lorenza; Candiani, Gabriele; Farè, Silvia; Boccaccini, Aldo R.; De Nardo, Luigi (Journal of Materials Science: Materials in Medicine, 2020)
Bioactive glasses (BGs), due to their ability to influence osteogenic cell functions, have become attractive materials to improve loaded and unloaded bone regeneration. BG systems can be easily doped with several metallic ions (e.g., Ag, Sr, Cu, Nb) in order to confer antibacterial properties. In particular, Nb, when compared with other metal ions, has been reported to be less cytotoxic and possess the ability to enhance mineralization process in human osteoblast populations. In this study, we co-deposited, through one-pot electrophoretic deposition (EPD), chitosan (CS), gelatin (GE) and a modified BG containing Nb to obtain substrates with antibacterial activity for unloaded bone regeneration. Self-standing composite scaffolds, with a defined porosity (15–90 μm) and homogeneous dispersion of BGs were obtained. TGA analysis revealed a BG loading of about 10% in the obtained scaffolds. The apatite formation ability of the scaffolds was evaluated in vitro in simulated body fluid (SBF). SEM observations, XRD and FT-IR spectra showed a slow (21–28 days) yet effective nucleation of CaP species on BGs. In particular, FT-IR peak around 603 cm−1 and XRD peak at 2θ = 32°, denoted the formation of a mineral phase after SBF immersion. In vitro biological investigation revealed that the release of Nb from composite scaffolds had no cytotoxic effects. Interestingly, BG-doped Nb scaffolds displayed antibacterial properties, reducing S. lutea and E. coli growth of ≈60% and ≈50%, respectively. Altogether, the obtained results disclose the produced composite scaffolds as promising materials with inherent antibacterial activity for bone tissue engineering applications. [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2020-05-08